Analisis Persaingan Merek Rokok Gudang Garam, Djarum dan HM Sampoerna Berdasarkan Ekuitas Merek Menggunakan Correspondance Analysis - Aini, Siti Dewi; Hidayat, Ahmad (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
In competing for market share, companies need to understand how their position lies not only in Brand Equity, but also in each indicator of Brand Equity. This study aims to analyze and determine the position and superiority of Gudang Garam, Djarum and HM Sampoerna cigarette brands based on Brand Equity variables consisting of Brand Awareness, Brand Association, Perception of Quality and Brand Loyalty and each indicator. This research was conducted in Medan Tembung District with sampling techniques using Nonprobability Sampling with Purposive Sampling approach. The analysis method used is Percentage Descriptive Analysis and Correspondance Analysis using IBM SPSS Statistic 23. The results showed that the level of cigarette brand competition did not have the same position and advantage in competition based on the Brand Equity variable and its indicators based on percentage Descriptive Analysis. In the results of Category Analysis the three cigarette brands do not have the same position and superiority in brand equity indicators and variables. But Gudang Garam and HM Sampoerna have the same advantage in the Brand Awareness indicator.